Pelatihan Pemasaran Digital Tokopedia Dalam Upaya Peningkatan Penjualan Kelompok Binaan Dinas Perikanan Cilacap - Nuni Wulansari; Indra Rachmawati; Laeli Farkhah; Adisa Refinatania Putri; Kuwera Dewi Shinta; Wilda Adelia Salsabila; Finda Nurlasih; Khansa Intah Fauziah (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2024)
The level of success of collaboration can be achieved when the collaboration involves people with diverse experiences, multi-disciplinary knowledge, different cultures, education and backgrounds. Various parties will present different thoughts and contributions, so that the problem will be handled from various angles in a comprehensive manner. The problem in Cilacap Regency, with the majority of coastal communities working as fishermen and fish processors, is that sales are stagnant because they only rely on traditional marketing, by selling fresh fish at TPI Padanarang or processing fish into crackers, salted fish, handicrafts that are sold directly at around TPI Pandanarang. The aim of this PkM is providing digital marketing training through Tokopedia as an effort to increase sales of groups supported by the Cilacap Fisheries Service. The method chosen was qualitative with the number of respondents being 10 residents representing groups supported by the Cilacap Fisheries Service. The results of the PkM which was at TPI Pandanarang - Teluk Penyu Area, South Cilacap District, Cilacap Regency were the creation of 10 Business Identification Numbers (NIB) and 10 online shop accounts on Tokopedia for 10 people representatives of groups supported by the Cilacap Regency Fisheries Service. Conclusions from field observations, apart from marketing training, it turns out that the community needs a lot of assistance when processing permits such as PIRT, halal certificates, promotional training, packaging design, hygiene and sanitation training, health safety food. The Cilacap District Fisheries Service can collaborate with several companies/agencies to get assistance with equipment grants, training from Corporate Social Responsibility (CSR) funds.